Role of MDCT in Diagnosis and Staging of Carcinoma Oesophagus - Sunita; Purohit Joshi, Swati; Choudhary, Neha; Kumar Mishra, Hemant (International Research in Medical and Health Sciences, 2021)
Background: Esophageal cancer is the eighth most common malignant tumor and the sixth most common cause of cancer death worldwide. Early detection of carcinoma esophagus and its appropriate staging can be life-saving for many patients. Multi-Detector Computed Tomography (MDCT) plays a crucial role in early detection, local invasion, and metastasis of carcinoma oesophagus, which also helps in appropriate staging and deciding a further plan of management. The present study describes various findings of oesophageal carcinoma on CT to aid in its staging.Materials and Methods: After ethical clearance, a retrospective and prospective hospital-based study were carried out in the Department of Radiodiagnosis, Mahatma Gandhi medical college and hospital Jaipur, Rajasthan, India over a period of last 5 years. After obtaining consent, 60 patients presenting with clinical symptoms and signs pertaining to carcinoma of oesophagus, were studied with a Multi-Detector CT scanner (128 slices GE Optima CT Machine) using thin sections. Oral and IV contrast was used. Three-dimensional reconstructions were done and various CT findings of oesophageal cancer were studied. The diagnosis and staging were confirmed by postoperative histopathological findings.Results: Carcinoma oesophagus was commonly seen in the age group between 60 to 70 years (35%) with males (63%) more commonly affected than females (37%). The most common presenting symptom was dysphagia. Alcohol and smoking were associated risk factors. The lower 1/3rd of oesophagus was affected more commonly compared to other parts. The wall thickness in a majority of the cases measured between 10-20mm (71.6%). T3N1M0 was the most common staging found in CT. Out of 60 cases 40% of cases presented with metastasis. Squamous cell carcinoma (80%) was the more common histopathological type. Out of 60patients when CT staging was compared with the postoperative histopathological staging, the sensitivity of CT-scan for ‘T 1-T2’ stage was 50%, for T3 stage was 73.5 %, in ‘N’ stage 81%, and in ‘M’ stage was 100%.Conclusion: MDCT is a modality of higher sensitivity and specificity for CA esophagus early diagnosis and staging. By early identification of loss of fat planes, detection of lymph nodal involvement, and metastasis to various organs with an overall diagnostic accuracy value of 74 to 84%, MDCT remains an outstanding tool in early diagnosis and staging of carcinoma oesophagus.